Matching and positivity beyond minimal coupling in effective theories of photons and gravitons - Edoardo Alviani; Adam Falkowski (European Physical Journal C: Particles and Fields)
Abstract We study the low-energy effective theories of photons and gravitons, matching them at one loop to a UV completion with a massive spinning matter particle. The matter is allowed to have non-minimal electromagnetic and gravitational interactions. We construct the one-loop 4-photon and 4-graviton helicity amplitudes with matter in the loop carrying anomalous multipole moments, and we read off the Wilson coefficients in the effective theory below the matter particle mass. Much as in the case of minimal coupling, the Wilson coefficients beyond the leading order turn out to be confined to small islands in the much larger theory space allowed by existing positivity constraints.